Fabrication of Silica Membrane through Surface‐Induced Condensation on Porous Block Copolymer. Issue 33 (6th September 2018) - Zhou, Meimei; Luo, Pingping; Li, Aowen; Wu, Yi‐nan; Khan, Muhammad Imran; Lyu, Jiqiang; Li, Fengting; Li, Guangtao
Abstract: Nanoporous structures generated from micro‐phase separation of block copolymers (BCPs) have been used as templates for fabrication of inorganic materials through atomic layer deposition (ALD), chemical vapor deposition, sol‐gel process, and electrodeposition. However, the previous deposition methods are suffering from unmanageable preparation conditions and demanding technical requirements. In this work, bioinspired synthesis was used as replicating technique to fabricate silica porous membrane on swelling‐induced polystyrene‐block‐poly (2‐vinyl pyridine) (PS‐b‐P2VP) membrane with bicontinuous nanopores. It was found that silica nanoporous membranes were successfully obtained on PS‐b‐P2VP under benign conditions (near‐neutral pH, low temperature, and ambient pressure) from tetraethoxysilane (TEOS). Moreover, the thickness of silica films could be regulated by the amount of water in the TEOS solution. The mechanism could be inferred that pyridine groups in P2VP domains can act as a catalyst for the insertion and polymerization reactions of silanol from hydrolysis of TEOS to form silica due to the hydrogen bonding between pyridine groups and Si‐OH in silanol. The proposed method offers a facile and controllable synthesis strategy to fabricate nanoporous silica membrane. Abstract : Nanoporous membrane with bicontinuous structure formed by microphase separation of polystyrene‐b‐poly(2‐vinylpyridine) (PS‐b‐P2VP) could be used as template/catalyst to fabricate silica membranes under mild conditions (near‐neutral pH, low temperature, and ambient pressure), with adjustable thickness of silica layer. Pyridine groups in P2VPdomain are inferred to provide reactive sites for catalyzing due to the hydrogen bonding between pyridine groups and silica precursors.